Relationship Between Plasma Total Homocysteine Levels and Mean Corrected TIMI Frame Count in Patients with Acute Myocardial Infarction - Hu F (Dove Medical Press, 2021)
Feng Hu,1 Feng Lu,2 Xiao Huang,1 Xiaoshu Cheng1 1The Department of Cardiovascular Medicine, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of China; 2The Department of Cardiothoracic Surgery, The Second Affiliated Hospital of Nanchang University, Nanchang, People’s Republic of ChinaCorrespondence: Xiao Huang; Xiaoshu ChengDepartment of Cardiovascular Medicine, The Second Affiliated Hospital of Nanchang University, No. 1 Minde Road, Nanchang, 330006, Jiangxi, People’s Republic of ChinaTel +8613607089128Fax +86-791-86262262Email drxiaohuang@163.com; xiaoshumenfan126@163.comObjective: To explore the relationship between the plasma total homocysteine (tHcy) levels and slow coronary flow (SCF) measured by mean corrected TIMI frame count (CTFC) in patients with acute myocardial infarction (AMI).Methods: Ninety-one patients with primary myocardial infarction were enrolled in this study. The quantitative measurement of coronary blood flow was performed using the mean CTFC method. Plasma tHcy levels were determined using enzymatic assay from venous blood samples. Multivariable linear regression models indicated were used to estimate the effect size (β) of plasma tHcy levels on mean CTFC levels.Results: Compared with patients with the mean CTFC ≤ 23.61 frames per second (FPS) group, there were increased plasma tHcy levels in patients of the second, third and highest mean CTFC quartiles (P < 0.001). Linear regression models indicated that plasma tHcy levels were positively associated with mean CTFC levels (adjusted-β per SD increase: 1.96, 95% CI 1.20 to 2.73, P < 0.001). Compared to the tHcy ≤ 12.30 μmol/L group, the third and highest tHcy-quartile groups had higher mean CTFC levels (adjusted-β: 2.52, 95% CI 0.39 to 4.65, P = 0.023; adjusted-β: 5.07, 95% CI 2.98 to 7.16, P < 0.001, respectively; P for trend < 0.001). Moreover, this positive relationship was modified by diabetes mellitus (P-value for interaction was 0.046).Conclusion: We found a positive relationship between plasma tHcy levels and mean CTFC levels in patients with AMI. Moreover, diabetes mellitus played an interactive role in this positive association between the plasma tHcy levels and mean CTFC levels.Keywords: hyperhomocysteinemia, mean corrected TIMI frame count, acute myocardial infarction, slow coronary flow, coronary microcirculation dysfunction